Extending Hospital-at-Home to nursing homes: findings from a novel care model in Singapore - Chong Yau Ong; Chong Yau Ong; Angus Jun Jie Ng; Hui Juan Ngo; Eunice Jia Hwei Ya; Jean Mui Hua Lee; Jean Mui Hua Lee (Frontiers in Public Health, 2025)
BackgroundWe implemented a Hospital-at-Nursing Home (HaNH) pilot program in a nursing home to reduce acute hospital bed utilization and allow residents to receive right-sited care in familiar environments.MethodsA prospective data collection of the Hospital-at-Home (HaH) program was conducted from November 2023 to December 2024 in a regional general hospital.Result16 HaNH enrollments were completed, comprising three admission avoidance cases and thirteen early supported discharges. Pneumonia (56.3%) and urinary tract infections (18.8%) were the most common diagnoses. The median length of stay was three days (range 1–12, IQR 4). One mortality occurred within the program in the HaNH in alignment with the patient’s preferred place of care and death, supported by palliative care. Comparisons with a non-institutionalized HaH cohort (n = 349) had a higher risk of escalation to the actual hospital facility (RR = 5.45, 95% CI: 1.71–17.42, p = 0.0025; aRR = 1.32, 95% CI: 0.35–4.96). HaNH patients had increased vulnerability, with higher post-discharge mortality (RR = 10.9, 95% CI: 2.16–55.21, p = 0.004; aRR = 3.38, 95% CI: 0.83–13.71) and emergency visits (RR = 3.18, 95% CI: 1.72–5.88, p = 0.0002; aRR = 2.00, 95% CI: 1.18–3.36), though readmission risk was non-significant.ConclusionThese preliminary findings suggest that while HaNH may alleviate hospital bed shortages, patients in nursing homes are at increased risk of deterioration and require careful selection and support.